One-Pot Palladium(II)-Catalyzed Synthesis of Fluorenones via Decarboxylative Cyclization - Cai, Zhiqiang; Hou, Xu; Hou, Ling; Hu, Zhiquan; Zhang, Bo; Jin, Zhengsheng (Synlett, 2016)
A one-pot palladium-catalyzed synthesis of fluoronones via decarboxylative cyclization is reported. This protocol offers good yields and tolerates a broad range of functional groups. Based on the extensive experimental data, we propose a plausible decarboxylative insertion mechanism.
Keywords: palladium-catalyzed; decarboxylative insertion; C–C cleavage; control experiment; mechanism